The impact of an upper tropospheric teleconnection pattern on precipitation extremes over Cyprus - Hatzaki, M.a; Lingis, P.b c; Flocas, H.A.a; Michaelides, S.b; Oikonomou, C.a (Advances in Geosciences, 2008)
The objective of this study is to estimate the duration, frequency and intensity of precipitation extreme episodes in Cyprus, in relation with the two phases of the Eastern Mediterranean teleconnection Pattern (EMP), during winter for the period 1958–2005. A standardised teleconnection index was employed to determine the phases (positive and negative) and the strength of the EMP. The identification of the precipitation extremes was performed with the aid of four climatic indices. It was found that during the positive phase of the pattern, the length of dry periods reduces while that of wet periods increases, being followed by increase of frequency of extreme wet days and precipitation intensity. On the contrary, during the negative phase, the dry spells become longer in accordance with shortening of the wet spells, decrease of the number of extreme wet days and precipitation intensity.
cited By (since 1996)1
Keywords: Asia; Cyprus; Eurasia; Middle East; precipitation intensity; teleconnection; troposphere